2018
DOI: 10.1007/s00373-018-1989-2
|View full text |Cite
|
Sign up to set email alerts
|

Properly Edge-colored Theta Graphs in Edge-colored Complete Graphs

Abstract: With respect to specific cycle-related problems, edge-colored graphs can be considered as a generalization of directed graphs. We show that properly edge-colored theta graphs play a key role in characterizing the difference between edge-colored complete graphs and multipartite tournaments. We also establish sufficient conditions for an edgecolored complete graph to contain a small and a large properly edge-colored theta graph, respectively. Keywords Edge-colored graph • Complete graph • Properly edge-colored c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Generalized Theta graphs, which have been widely studied for many graph theoretic problems (see e.g., [8,11,14,22,23,27]), are the main subject of two classical papers on the chromatic polynomial [10] and [28] which include the celebrated result that the zeros of the chromatic polynomials of the Generalized Theta graphs are dense in the whole complex plane with the possible exception of the unit disc around the origin (by including the join of Generalized Theta graphs with K 2 this extends to all of the complex plane). It is natural to study the DP color function of these graphs, independent of our motivating questions.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Generalized Theta graphs, which have been widely studied for many graph theoretic problems (see e.g., [8,11,14,22,23,27]), are the main subject of two classical papers on the chromatic polynomial [10] and [28] which include the celebrated result that the zeros of the chromatic polynomials of the Generalized Theta graphs are dense in the whole complex plane with the possible exception of the unit disc around the origin (by including the join of Generalized Theta graphs with K 2 this extends to all of the complex plane). It is natural to study the DP color function of these graphs, independent of our motivating questions.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Although Li et al [13] and later Xu et al [21] have got pr(K n , C 4 ) = n for n ≥ 4, here we will use a different method to prove it again. We denote a cycle C k with a pendant edge by C + k .…”
Section: Cyclesmentioning
confidence: 92%
“…It is easy to see that pr(K n , C 3 ) = ar(K n , C 3 ) = n − 1. Li, Broersma and Zhang [13], and later Xu, Magnant, and Zhang [21] showed that pr(K n , C 4 ) = n for n ≥ 4. We consider C 5 and C 6 in section 4.…”
mentioning
confidence: 96%
“…in polynomial time. This has been the topic of many papers in the past, see e.g [4,7,8,9,10,11,12,17,18,19,22].…”
Section: Introductionmentioning
confidence: 99%